Abuso sexual: vítimas das relações familiares - Santos, Noêlia Oliveira Dias dos (1995)
This study was realized from a quantitative survey with the aims of to determine the associated factors involved in sexual abuse complains that occur in family relationship, , and analyse this kind of delict under the point of view of gender and power relations. The population studied was intentionally sorteei includind all cases that were notified as child sexual abuse involving male or female children under 20 , and that were submited to legal medicai examination during the period of 5 years. The study was rnade in 482 cases. The analyse confirmed that for each male child there are eighteen female children with complain of sexual abuse and the main acoused as responsible for this crime are stepfalturs in prime place followed for falhers what .reved one disçriminative involvement of gender in this relationship.